Flexible Hydrogen Peroxide Sensors Based on Platinum Modified Free-Standing Reduced Graphene Oxide Paper - Run-Min Song; Zhan-Hong Li; Peng-Ju Wei; Xue-Ling Zhao; Cheng Chen; Zhi-Gang Zhu (Applied Sciences, 2018)
In this article, we report a facile method to fabricate free-standing reduced graphene oxide paper (rGOP) by vacuum filtration. Pt nanoparticles were electrodeposited on reduced graphene oxide paper to construct a sensitive and flexible hydrogen peroxide (H2O2) sensor. The properties of Pt/rGOP were characterized by scanning electron microscopy, energy dispersive X-ray, X-ray photoelectron spectroscopy and Raman spectroscopy. The electrochemical characterizations of the resulting sensor were carried out by cyclic voltammetry, chronoamperometry and electrochemical impedance spectroscopy. The Pt/rGOP hybrid electrode had an excellent electrochemical property, with superb electrocatalytic activity, a large electrochemical active surface area, flexibility and high stability. The linear ranges of the as-prepared sensor for H2O2 detection were divided into two linear sections: 0.2 μmol/L to 2.0 mmol/L and 2.0 to 8.5 mmol/L, with a detection limit of 100 nmol/L (S/N = 3) and a response time of less than 5 s. The proposed sensor has great potential to become a reliable and flexible tool in biosensor and point-of-care medical devices.